Odpowiedzi

2010-01-03T17:23:25+01:00
-[1-(x-y)²]-[(y-x)²-1]=[(x-y)²-1]-[(y-x)²-1]=0

(x-3)(x-3)-(x-1)(x-1)+4(x-2)=x²-6x+9-x²+2x-1+4x-8=0
Najlepsza Odpowiedź!
2010-01-03T17:24:32+01:00
W obu przykładach musimu skorzystać ze wzorów skróconego mnożenia:
1. (x - y)² = x² -2xy + y²
2. (x + y)² = x² + 2xy +y²


-[1-(x-y)²]-[(y-x)²-1] = -[1 - ( x² -2xy + y²)] - [( y² - 2xy + x²) - 1] =
= - [1 - x²+ 2xy - y²] - [y² - 2xy + x² - 1] =
= -1 +x² -2xy + y² - y² + 2xy - x² + 1 =
= +x² - x² - 2xy + 2xy + y² - y² -1 + 1 = 0

(x-3)(x-3)-(x-1)(x-1)+4(x-2)= (x - 3)² - (x - 1)² + 4x - 8 =
= x² -2x*3 + 3² - ( x² -2x*1 + 1²) + 4x - 8 =
= x² -6x + 9 - x² + 2x - 1 + 4x - 8 = x²- x² -6x + 2x + 4x + 9 - 1 - 8 = 0